Synchronous control for multiple electrohydraulic actuators with feedback linearization. (1st October 2022) - Guo, Qing; Chen, Zhenlei; Shi, Yan; Li, Xiaochai; Yan, Yao; Guo, Fan; Li, Shuai
Abstract: Based on some research of electrichydraulic servo system (EHSS), the synchronous control problem of multiple electrohydraulic actuators (MEHAs) is investigated to guarantee the MEHAs' system stability and leader-following synchronization with third-order nonlinear dynamics and unknown external load. Firstly, the EHA model is linearized by Lie derivatives technique to obtain the third-order linear isomorphic model of MEHAs with unknown external load. Then the disturbance observer is adopted to estimate unknown external load caused by the driven force of mechanical plant. Meanwhile, the state-feedback matrix is firstly designed by pole placement technique to guarantee the feedback linearization model Hurwitz. Furthermore, the synchronous controller is designed by Lyapunov technique and LMI to guarantee that n EHAs follower states synchronize the leader state with arbitrarily small zeros neighborhood under directed spanning tree. The effectiveness of the synchronous controller is verified by both comparative simulation and experimental bench. Highlights: A synchronous control is used to realize the state synchronization of multiple EHAs nodes. By using the feedback linearization, the state space model of MEHAs is constructed. The disturbance observer is modeled to estimate unknown external load. The synchronous controller is designed by Lyapunov and LMI techniques.